Disability sports from charity towards partnerships-case: The Finnish Paralympic Committee - Maekynen, T. (Haaga-Helia University of Applied Sciences, 2020)
The main goal of this Master ´s Thesis is to analysewhat motivates the business stakehold-ers to support disability sport. Futuresupport from the government is uncertain so thereis a huge need for this study to understand and attract more business stakeholdersto sup-port sportsfor people with disabilitiesin Finland.The Finnish Paralympic Committee (Suomen Paralympiakomitea ry) and the Finnish Sports Association forPersons with Disabilities (VAU ry) merged on1.1.2020 formingone large disability sports organisation in Finland. Until 2019, theFinnish Paralympic Commit-tee supported mainly elite sportingactivities. From 2020,the newly formed Paralympic Committee supportsabroad perspective of sports activities for peoplewith disabilities.What are the existing business partners` reasonsfor cooperation? What do thepartnersexpectfrom future cooperation with disability sports?This studygivesconcrete sugges-tionsto improve business stakeholder communication to helpassociations, organizations,clubsandathletestoattract more business partnersto support disability sports.Thenewnon-governmental umbrella of disability sportorganization requiresitsown strong fundraising operations and strategyto be able to support disability sports from children`sto adults`and from hobbyactivitiesto elite sports. The subject is highly important as the Para-lympic Committeeseeks to support its members and otherorganizationsorganizing disa-bility sports. Better understanding ofbusiness stakeholders willhave a hugeinfluence onthefutureof disability sportssupport.The literaturereviewcoversstakeholder communication, stakeholder managementand corporate social responsibility (CSR).Thestudy notesthe special role of these theories inthe non-profit and sports organizationenvironmentat the same timeas itexplainsthespe-cial role of disability sport andthe importance of theParalympic movement.Theresearch isbased on acase study methodwithaconstructiveapproach. The primarydata consisted of semi-structuredinterviewswithexisting business stakeholders,which took place before the formationof the new organization. The analysis of the data draws onqualitative methods andquantification.The discussion explainstheconcrete findings and suggestsapartnership stakeholder model based onthe frameworkof aKey Account Management Relational Development Model.Supportingdisabilitysports bringsvalue for business stakeholdersandis important fortheircorporate social responsibility(CSR)and brand image.All the interviewed partners (100%) would recommend cooperation with the Paralympic Committee to other compa-nies. In the future,many companiesin Finland couldbenefit from cooperationwith disabled athletesand be part of the fundamental change from charity towards partnerships.